Effect of endurance training on adrenergic control of lipolysis in adipose tissue of obese women - Richterova, B; Stich, V; Moro, C; Polak, J; Klimcakova, E; Majercik, M; Harant, I; Viguerie, N; Crampes, F; Langin, D; Lafontan, M; Berlan, M (The Journal of clinical endocrinology and metabolism, 2004)
The effect of a 12-wk training program on sc abdominal adipose tissue (SCAAT) was studied in 11 obese women. Before and after the training, biopsies of SCAAT were performed for mRNA levels determination. Using the microdialysis method, involvement of alpha(2)- and beta-adrenergic receptor (ARs) in the control of lipolysis in SCAAT was studied using local perfusion of epinephrine alone or supplemented with phentolamine, an alpha(2)-AR antagonist. In addition, the variation in dialysate glycerol concentrations during exercise (50% peak oxygen consumption at 40 min) in a probe perfused with Ringer's solution was compared with that obtained in a probe perfused with Ringer's solution plus phentolamine. Training did not promote changes in the expression of key genes of the lipolytic pathway. The epinephrine-induced rise in the dialysate glycerol concentration was identical before and after training and was similarly potentiated by phentolamine. During exercise, the potentiating effect of phentolamine on the glycerol response was apparent before, but not after, training. The exercise-induced increase in plasma norepinephrine was lower after training (P = 0.04). In conclusion, training did not modify either the expression of genes involved in the control of lipolysis or alpha(2)- and beta-ARs in situ sensitivity to epinephrine in SCAAT. Training reduced the antilipolytic action of catecholamines mediated by alpha(2)-ARs during exercise, probably due to a reduction of exercise-induced catecholamine increase.
Keywords: index tělesné hmotnosti; Receptors, Adrenergic, alpha-2; messenger RNA; alfa-2-adrenergní receptory; Adrenergic Agonists; Glycerol; Fatty Acids, Nonesterified; Obesity; krevní glukóza; fyzická vytrvalost; spotřeba kyslíku; Oxygen Consumption; Receptors, Adrenergic, beta; břicho; inzulin; Insulin; Epinephrine; Adult; Lipolysis; Abdomen; noradrenalin; Body Mass Index; polymerázová řetězová reakce s reverzní transkripcí; Blood Glucose; ženské pohlaví; Gene Expression; RNA, Messenger; adrenalin; Humans; Physical Endurance; Rest; odpočinek; Adipose Tissue; obezita; glycerol; exprese genu; Reverse Transcriptase Polymerase Chain Reaction; kyseliny mastné neesterifikované; dospělí; Norepinephrine; agonisté adrenergních receptorů; Female; tuková tkáň; lipolýza; beta-adrenergní receptory; lidé